Pro-inflammatory effects of endogenous and recombinant MDA-7/IL-24 with RGD peptide on human hepatic stellate cells - Afrooz Daneshparvar; Seyed Younes Hosseini; Nasrin Hamidizadeh; Mohabbat Jamhiri; Nader Tanideh; Maryam Sadat Sadati; Iman Jamhiri (Scientific Reports)
Abstract Hepatic stellate cells (HSCs) serve as pivotal mediators of liver fibrogenesis. This study investigates the pro-inflammatory effects of melanoma differentiation-associated gene-7/interleukin-24 (MDA-7/IL-24) within both murine and cellular models. By employing the hydrodynamic injection of a plasmid expressing IL-24/mda7 (PMDA-7) in mice, significant inflammatory histopathological alterations were observed in the liver tissue. In human LX-2 HSCs, treatment with recombinant IL-24 (rIL-24), as well as transfection with PMDA-7 or RGD-modified PMDA-7-RGD plasmids, resulted in an increased expression of pro-inflammatory cytokines (IL-1β, IL-6, IL-17, IL-18, IL-23) and regulatory molecules (SOCS1, SOCS3). Importantly, the RGD-modified variant exhibited the most pronounced effects, with PMDA-7-RGD inducing the highest levels of IL-1β, IL-6, IL-17, and IL-18 expression, whereas rIL-24 was noted to most effectively upregulate IL-23 (P < 0.05). These findings substantiate that MDA-7/IL-24 exerts pro-inflammatory effects on HSCs, which are further amplified by RGD conjugation, thus suggesting its potential involvement in the pathogenesis of liver inflammation and fibrosis.